Perencanaan Struktur Gedung 5 Lantai Menggunakan Balok dan Pelat Prategang Sesuai SNI 2847 2013 - Pratama, Deska Adi; Sebayang, Surya; Irianti, Laksmi (Universitas Lampung, 2018)
In multistorey building construction there are many types structural system that are being used such as reinforced concrete system, prestressed concrete system and composite system with its advantages in disadvantages. The purpose of this research was for designing 5 storey building using prestressed concrete for beams and slabs with SNI 2847-2013. From analysis results, the dimension of hollow core slab is 1200 x 7500 x 250 mm with Ø12,7-300 strands. The reinforcement of non prestressed HCS are Ø16-250 for main reinforcement and Ø13-300 for cross reinforcement. The 15 m span prestressed beam has dimension 800 x 500 mm with 24-Ø12,7 strands. Shear and torsion design with Ø16-140 as stirrups and 8D19 as longitudinal reinforcement. The 7,5 m span prestressed beam has dimension 600 x 425 mm with 4-Ø12,7 strands. Shear and torsion design with Ø16-100 as stirrups and 10D19 as longitudinal reinforcement. The dimension of column is 600 x 600 mm with 26-D22 as main reinforcement and Ø16-175 for shear reinforcement on maximum load. In prestressed system design that applied for beam and slab based on SNI 2847-2013 on 5 storeys building has much smaller rebar percentage than normal reinforced system.